Sociodemographic determinants of life satisfaction among grandparent caregivers - Xu, Yi; Zhang, Ling; Mao, Shuyuan; Zhang, Si; Peng, Shuzhen; Zhang, Qi; Wu, Wenwen; Tan, Xiaodong (Frontiers in Public Health, 2023)
Abstract: Nowadays, it has become a common phenomenon for grandparents to look after young children in the family in both urban and rural areas. This study attempted to investigate the psychological state and life status, and explore the relationships between socio-demographic characteristics, life status and life satisfaction of grandparents involved in childcare in China. With a stratified random cluster sampling, we conducted a survey among grandparent caregivers from November, 2020 to December 2020 in Wuhan (N=1,640). Descriptive analysis, univariate analysis, multiple linear regression and structural equation model were used. The mean scores of life satisfaction, sleep quality and life quality of all respondents were 14.05±3.50, 5.02±3.37 and 74.51±16.88, respectively. Marital status, income, chronic diseases, family relationships and physical exercise were found to be associated with life satisfaction. Structural equation modeling results showed that life quality, sleep quality and socio-demographic characteristics may affect life satisfaction directly or indirectly. The mediating effects accounted for 30.0% of the total. Grandparent caregivers suffered from poor life satisfaction, life quality and sleep quality. Elevated household income, better family relationships among family members, healthy lifestyle habits, as well as good sleep quality may effectively help improve life satisfaction of grandparent caregivers.